2018
DOI: 10.1590/1518-8345.2482.3080
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety of mothers of newborns with congenital malformations in the pre- and postnatal periods

Abstract: Objective:to analyze the anxiety level of the mothers of newborns with congenital malformations who were diagnosed in prenatal and postnatal care. Methods:a cross-sectional study with 115 mothers of 117 newborns with congenital malformation admitted to three neonatal units. A questionnaire containing maternal and neonatal variables was used, as well as the Trait-State Anxiety Inventory. Data were analyzed by Student’s t-test and Kolmogorov-Sminorv test. The anxiety level was categorized as low (percentile <25)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 21 publications
3
10
0
5
Order By: Relevance
“…The results of this study showed that mothers of gastrointestinal anomalies suffered from a high level of anxiety in the first day of anomaly diagnosis. Anxiety is one of the emotional distresses in mothers of infants with anomalies, which can delay the relationship between mothers and their newborns (8,(22)(23)(24). Therefore, health care professionals should assess the emotional state of mothers following the birth of congenital anomalies and provide parents the required information in this regard (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed that mothers of gastrointestinal anomalies suffered from a high level of anxiety in the first day of anomaly diagnosis. Anxiety is one of the emotional distresses in mothers of infants with anomalies, which can delay the relationship between mothers and their newborns (8,(22)(23)(24). Therefore, health care professionals should assess the emotional state of mothers following the birth of congenital anomalies and provide parents the required information in this regard (25).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study's Fonseca et al (2012) show that parents of newborns with congenital anomalies experience a high level of anxiety and depression (7). Another study in Brazil demonstrated that most mothers with abnormal newborn, had a moderate level of anxiety; however, the anxiety levels were higher in mothers who had a diagnosis of postpartum anomalies (8).…”
Section: Introductionmentioning
confidence: 93%
“…O escore total para o somatório dos 20 itens para cada participante varia de 20-80 pontos. A classificação adotada para os níveis de ansiedade foram graus: baixo (0-34 pontos), moderado (35-49), alto (50-64) e muito alto (65-80) (Fontoura, Cardoso, Rodrigues, Almeida & Carvalho, 2018). Vale ressaltar que o estudo não objetivou diagnosticar a ansiedade como transtorno, considerando que esta é uma atribuição médica, mas enquanto variável identificada pela classificação dos graus deste transtorno emergentes nos somatórios de um instrumento multidisciplinar.…”
Section: Metodologiaunclassified
“…In addition, prenatal identification of CHDs allows referral of patients hospitals with neonatal intensive care units and expertise in neonatal management of these conditions. Finally, early screening (regardless of positive or negative results) significantly reduces maternal anxiety 13 . In the field of prenatal diagnosis, the utility of metabolomics is being realized and increasing in application 14‐18 .…”
Section: Introductionmentioning
confidence: 99%